Translating words into numbers measuring media sentiment and its effect on the Philippine Stock Exchange - Benitez, Eryel Nicole S. (School of Economics, University of the Philippines Diliman, 2018)
In today_s online world, news can be easily disseminated within an instant making them readily available to investors. These news reports can easily influence investors and affect the stock market price and volume. This paper examines whether media sentiment, which is a proxy to investor sentiment, influences the different sectors of the Philippine Stock Exchange using vector autoregression model. We have constructed a Philippine news article archive from 2013 to 2017, and the analyzed it through R using the Loughran McDonald dictionary _ creating the Philippine media sentiment index. Vector Autoregression was used to test the relationship of stock returns, trade volume, and media sentiment to one another. We use the maximum lag of 5, a week worth of trading days, for each equation. The trade volume of Financial sector and Industrial sector and the daily returns of the Mining and Oil sector are more sensitive to sentiment than the other sectors.